GE_GERICHTE C/26472/2011 vom 25. September 2015 - GE Cour de justice (2015)
VENTE; PRIX; REMISE CONVENTIONNELLE DE DETTE; INTÉRÊT MORATOIRE; LÉGITIMATION ACTIVE ET PASSIVE | CO.104.1; CO.115; CO.143.1; CO.184